THEORETICAL FOUNDATIONS OF THE USE OF MODERN GIS TECHNOLOGIES IN THE CREATION OF NATURAL MAPS - Gulshanoy Mirzakarimova (Western European Studies, 2024)
this article examines the theoretical basis for the use of modern Geographic Information Systems (GIS) technologies in the creation of natural maps. The study analyzes the role and importance of GIS technologies in natural resource management, environmental monitoring and territorial planning. As methodological approaches, the components of GIS technologies, their integration and methods of data analysis were studied
Keywords: GIS technologies; natural maps; environmental monitoring